Computational prediction of Mg-isotope fractionation between aqueous [Mg(OH2)6]2+ and brucite. (15th April 2018) - Colla, Christopher A.; Casey, William H.; Ohlin, C. André
Abstract: The fractionation factor in the magnesium-isotope fractionation between aqueous solutions of magnesium and brucite changes sign with increasing temperature, as uncovered by recent experiments. To understand this behavior, the Reduced Partition Function Ratios and isotopic fractionation factors (Δ 26/24 Mgbrucite-Mg(aq) ) are calculated using molecular models of aqueous [Mg(OH2 )6 ] 2+ and the mineral brucite at increasing levels of density functional theory. The calculations were carried out on the [Mg(OH2 )6 ] 2+ ·12H2 O cluster, along with different Pauling-bond-strength-conserving models of the mineral lattice of brucite. Three conclusions were reached: (i) all levels of theory overestimate 〈MgO〉 bond distances in the aqua ion complex relative to Tutton's salts; (ii) the calculations predict that brucite at 298.15 K is always enriched in the heavy isotope, in contrast with experimental observations; (iii) the temperature dependencies of Wimpenny et al. (2014) and Li et al. (2014) could only be achieved by fixing the 〈MgO〉 bond distances in the [Mg(OH2 )6 ] 2+ ·12H2 O cluster to values close to those observed in crystals that trap the hydrated ion.